Lithium ion secondary battery and electric device
By using high-molecular-weight polyacrylate binder and dispersant in the positive electrode film layer of lithium-ion secondary batteries, combined with the primer technology, the serious self-discharge problem of lithium-containing phosphate secondary batteries has been solved, and the battery has been improved storage performance and energy density.
Patent Information
- Application Number
- CN202411625228.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2024-12-13
AI Technical Summary
High-energy density lithium-ion secondary batteries contain lithium phosphate and have serious self-discharge problems during storage, resulting in a gradual decline in battery capacity and affecting storage performance.
Polyacrylate binders with a weight average molecular weight of 800,000 Daltons to 1.3 million Daltons are used to combine lithium-containing phosphate and dispersant to form a positive electrode film with high bonding and cohesive force to reduce powder loss , and the adhesion and pressure sensitive characteristics of the electrode sheet are improved by the primer layer.
It effectively reduces the self-discharge of the battery, improves the storage performance and energy density of the battery, enhances the adhesion and cohesion of the electrode sheet, and reduces the powder loss problem during die cutting, winding and hot pressing.
Smart Images

Figure CN119133459A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of secondary batteries, and in particular to a lithium-ion secondary battery and an electrical device. Background Art
[0002] In recent years, as the application scope of secondary batteries becomes wider and wider, secondary batteries are widely used in energy storage power supply systems such as hydropower, thermal power, wind power and solar power stations, as well as in many fields such as electric tools, electric bicycles, electric motorcycles and electric vehicles.
[0003] Secondary batteries using lithium phosphates such as lithium iron phosphate (LFP) as positive electrode active materials have the advantages of low cost and good safety, and have become a hot area for secondary battery development. With the rapid development of secondary battery technology, higher requirements have been placed on the energy density of secondary batteries. How to further improve the energy density of secondary batteries using lithium phosphates as positive electrode active materials has become one of the important research directions in this field.
[0004] However, an important problem faced by high energy density lithium phosphate secondary batteries is that the self-discharge phenomenon of the battery is relatively serious. The capacity of the battery will gradually decrease during storage, affecting the storage performance of the battery. Therefore, how to reduce the self-discharge of lithium phosphate secondary batteries and improve battery performance while increasing the energy density of lithium phosphate secondary batteries is one of the key areas of focus for those skilled in the art. Summary of the invention
[0005] The present application is made in view of the above-mentioned problems, and one of its purposes is to provide a lithium-ion secondary battery and an electric device with low battery self-discharge.
[0006] In order to achieve the above-mentioned object, the first aspect of the present application provides a lithium-ion secondary battery, comprising a positive electrode plate, wherein the positive electrode plate comprises a positive electrode current collector and a positive electrode film layer provided on at least one side of the positive electrode current collector, and the coating surface density of the positive electrode film layer on one side is 20 mg / cm 2 ~30mg / cm 2 The positive electrode film layer includes lithium phosphate and polyacrylate binder, the weight average molecular weight of the polyacrylate binder is 800,000 Daltons to 1.3 million Daltons; the compaction density of the positive electrode sheet is 2.45 g / cm 3 ~2.55g / cm 3 .
[0007] By using a polyacrylate binder with a weight average molecular weight of 800,000 Daltons to 1.3 million Daltons in the positive electrode film layer; the polyacrylate binder with the above molecular weight has a longer polymer molecular chain, more contact points between molecules, stronger interaction force, and higher cohesive force. When the coating surface density and compaction density of the positive electrode film layer are large, it can play a good bonding role on the lithium-containing phosphate in the positive electrode film layer, and can make the positive electrode plate have higher bonding force and cohesive force, reduce or avoid the problem of positive electrode film layer powder falling off easily during die-cutting, winding and hot pressing of the positive electrode plate, thereby reducing battery self-discharge.
[0008] In any embodiment, the weight average molecular weight of the polyacrylate binder is 1 million Daltons to 1.3 million Daltons. This is conducive to further improving the bonding and cohesive force of the pole piece, further improving the problem of pole piece powder falling, and also better reducing the self-discharge of the battery.
[0009] In any embodiment, the polyacrylate binder includes a structural unit derived from an acrylate monomer, and the acrylate monomer includes one or more of methyl methacrylate, butyl acrylate, or isooctyl acrylate.
[0010] In any embodiment, the mass proportion of the structural unit derived from the acrylic ester monomer in the polyacrylate binder is 60% to 80%.
[0011] In any embodiment, the polyacrylate adhesive further comprises a structural unit derived from a first monomer, wherein the first monomer comprises one or more of styrene or acrylonitrile, which is beneficial to improving the cohesive force of the pole piece.
[0012] In any embodiment, the mass proportion of the structural unit derived from the first monomer in the polyacrylate binder is 20% to 40%.
[0013] In any embodiment, based on the total mass of the positive electrode film layer being 100%, the mass fraction of the polyacrylate binder is 1% to 2%. This is beneficial for improving the bonding and cohesive force of the electrode sheet while taking into account the energy density of the battery.
[0014] In any embodiment, the Dv50 particle size of the lithium-containing phosphate is 1.1 μm to 1.8 μm. The use of the lithium-containing phosphate with the above-mentioned Dv50 particle size is conducive to shortening the transmission distance of lithium ions and electrons, and is conducive to the energy output of high-energy-density lithium-ion secondary batteries. The polyacrylate binder of the present application has good adhesion to the lithium-containing phosphate, and the lithium-containing phosphate is combined with the binder to obtain a high-energy-density lithium-containing phosphate lithium-ion secondary battery with low self-discharge.
[0015] In any embodiment, the positive electrode film layer further includes a dispersant, and the dispersant includes one or more of a phosphate compound, a styrene-ethylene / butylene-styrene block copolymer, or a hydrogenated nitrile rubber. By introducing the above dispersant, the problem of gelation of the positive electrode slurry including a polyacrylate binder and a lithium phosphate can be effectively alleviated, which is conducive to improving the dispersion uniformity and coating uniformity of the slurry.
[0016] In any embodiment, based on the total mass of the positive electrode film layer being 100%, the mass fraction of the dispersant is 0.3% to 0.5%, which is beneficial for further dispersing the polyacrylate binder and the lithium-containing phosphate and inhibiting the gelation of the positive electrode slurry.
[0017] In any embodiment, the positive electrode plate further comprises a positive electrode current collector and a primer layer, wherein the primer layer is disposed between the positive electrode current collector and the positive electrode film layer, and the primer layer comprises a conductive agent and a polar group grafted modified polymer binder, wherein the polar group comprises a carboxyl group and / or an ester group. This is conducive to further improving the bonding force of the positive electrode plate and further improving the problem of the plate powder falling off.
[0018] In any embodiment, the polar group graft-modified polymer binder includes a structural unit derived from a second monomer and a structural unit derived from a third monomer; the second monomer and the third monomer are of different monomer types;
[0019] The second monomer includes one or more of styrene or acrylonitrile;
[0020] The third monomer includes one or more of ethylene, propylene, butadiene, isoprene or acrylonitrile.
[0021] In any embodiment, the polar group grafted modified polymer binder includes one or more of polar group grafted modified styrene-ethylene / butylene-styrene block copolymer, polar group grafted modified hydrogenated styrene-butadiene rubber, polar group grafted modified styrene-isoprene-styrene block copolymer or polar group grafted modified styrene-ethylene-propylene-styrene type block copolymer. In this way, it is beneficial to have good adhesion between the primer layer and the positive electrode film layer, and at the same time, the positive electrode plate has certain pressure-sensitive characteristics, which helps to improve the charge transfer efficiency and can better adapt to the pressure changes inside the battery.
[0022] In any embodiment, the polar group graft-modified polymer binder includes a structural unit derived from a fourth monomer containing a polar group, and the fourth monomer includes one or more of acrylic acid, methyl methacrylate, butyl acrylate, isooctyl acrylate or maleic anhydride.
[0023] In any embodiment, based on the total mass of the primer layer being 100%, the mass fraction of the polar group-grafted polymer binder is 50% to 70%, which is conducive to good adhesion between the primer layer and the positive electrode current collector and the positive electrode film layer.
[0024] In any embodiment, the thickness of the primer layer is 1 μm to 2 μm.
[0025] In any embodiment, based on the total mass of the positive electrode film layer being 100%, the mass fraction of the lithium-containing phosphate is 90% to 99%.
[0026] In any embodiment, the lithium-containing phosphate includes one or more of lithium iron phosphate, lithium manganese phosphate or lithium manganese iron phosphate.
[0027] In a second aspect of the present application, there is provided an electrical device comprising the lithium-ion secondary battery of the first aspect of the present application.
[0028] The details of one or more embodiments of the present application are set forth in the following drawings and description. Other features, objects, and advantages of the present application will become apparent from the description, drawings, and claims. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to better describe and illustrate the embodiments or examples provided by the present application, reference may be made to one or more drawings. The additional details or examples used to describe the drawings should not be considered as limiting the scope of the disclosed application, the embodiments or examples currently described, and any of the best modes of these applications currently understood. Moreover, the same reference numerals are used throughout the drawings to represent the same components. In the drawings:
[0030] Figure 1 A schematic diagram of a battery cell according to an embodiment of the present application;
[0031] Figure 2 for Figure 1 An exploded view of a battery cell according to an embodiment of the present application is shown;
[0032] Figure 3 A schematic diagram of an electrical device using a lithium-ion secondary battery according to an embodiment of the present application as a power source.
[0033] Description of reference numerals:
[0034] 5. Battery cell; 51. Shell; 52. Electrode assembly; 53. Cover plate; 6. Electrical device. DETAILED DESCRIPTION
[0035] Hereinafter, the embodiments of the lithium-ion secondary battery and the electric device of the present application are described in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0036] The "range" disclosed in the present application can be limited in the form of a lower limit and an upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The range limited in this way can be including or excluding end values, and any end value can be included or not included independently, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range. For example, if a range of 60 to 120 and 80 to 110 is listed for a specific parameter, it is understood that the range of 60 to 110 and 80 to 120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are also listed, the following ranges can all be expected: 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4 and 2 to 5. In the present application, unless otherwise specified, the numerical range "a to b" represents the abbreviation of any real number combination between a and b, wherein a and b are both real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to listing the parameter as, for example, integers 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc. For example, when a parameter is expressed as an integer selected from "2-10", it is equivalent to listing the integers 2, 3, 4, 5, 6, 7, 8, 9 and 10.
[0037] In the present application, "plurality", "multiple" and the like, unless otherwise specified, refer to a number greater than or equal to 2. For example, "one or more" means one or greater than or equal to two.
[0038] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0039] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment or implementation of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments. The "implementation methods" mentioned herein have a similar understanding.
[0040] Those skilled in the art will appreciate that, in the methods of each embodiment or example, the order in which each step is written does not mean a strict order of execution and does not constitute any limitation on the implementation process, and the detailed order of execution of each step should be determined by its function and possible internal logic. If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or steps (b) and (a) performed sequentially. For example, the method may also include step (c), indicating that step (c) can be added to the method in any order, for example, the method may include steps (a), (b) and (c), or steps (a), (c) and (b), or steps (c), (a) and (b), etc.
[0041] In the present application, in the open technical features or technical solutions described by the words "contain", "include", "comprise", etc., unless otherwise specified, additional members other than the listed members are not excluded, and it can be regarded as providing both closed features or solutions consisting of the listed members and open features or solutions including additional members in addition to the listed members. For example, A includes a1, a2 and a3. Unless otherwise specified, it may also include other members or may not include additional members. It can be regarded as providing both the feature or solution of "A consists of a1, a2 and a3" and the feature or solution of "A not only includes a1, a2 and a3, but also includes other members". In the present application, unless otherwise specified, A (such as B) means that B is a non-limiting example of A, and it can be understood that A is not limited to B.
[0042] In this application, "optionally", "optional", and "optional" mean optional, that is, any one of the two parallel schemes of "yes" or "no". If there are multiple "options" in a technical solution, unless otherwise specified and there is no contradiction or mutual restriction, each "option" is independent.
[0043] Secondary batteries using lithium iron phosphate and other lithium-containing phosphates as positive electrode active materials have the advantages of low cost and good safety, and have become a hot area for secondary battery development. With the rapid development of secondary battery technology, higher requirements have been placed on the energy density of secondary batteries. How to further improve the energy density of secondary batteries using lithium-containing phosphates as positive electrode active materials has become one of the important research directions in this field. However, an important problem facing high-energy-density lithium-ion secondary batteries containing lithium phosphates is that the self-discharge phenomenon of the battery is relatively serious, and the capacity of the battery will gradually decrease during storage, affecting the storage performance of the battery. The main reason is that high-energy-density lithium-phosphate-containing lithium-ion secondary batteries usually require a larger positive electrode film coating surface density and a larger compaction density. In order to firmly bond the active material, conductive agent and other particles together, higher requirements are placed on the bonding force and cohesion of the binder used in the positive electrode film layer. Conventional binders have insufficient bonding force and cohesion with lithium-phosphate-containing positive electrode materials when the positive electrode film layer has a large coating surface density, which leads to the positive electrode film layer easily shedding powder during the die-cutting, winding and hot pressing processes of the positive electrode sheet, causing self-discharge of the lithium-ion secondary battery.
[0044] In this regard, an embodiment of the present application provides a lithium-ion secondary battery, the lithium-ion secondary battery comprising a positive electrode plate, the positive electrode plate comprising a positive electrode current collector and a positive electrode film layer disposed on at least one side of the positive electrode current collector, and the coating surface density of the single-side positive electrode film layer is 20 mg / cm 2 ~30mg / cm 2 The positive electrode film layer includes lithium phosphate and polyacrylate binder; the weight average molecular weight of the polyacrylate binder is 800,000 Daltons to 1.3 million Daltons; the compaction density of the positive electrode sheet is 2.45g / cm 3 ~2.55g / cm 3 .
[0045] The lithium-ion secondary battery mentioned above in the present application adopts a polyacrylate binder with a weight-average molecular weight of 800,000 Daltons to 1.3 million Daltons in the positive electrode film layer; wherein the polyacrylate binder with a weight-average molecular weight of 800,000 Daltons to 1.3 million Daltons has a relatively long polymer molecular chain, has more contact points between molecules, and has a relatively strong interaction force. It has a relatively high bonding force and cohesive force for the lithium-containing phosphate positive electrode material. When the coating surface density and compaction density of the positive electrode film layer are relatively large, it can play a good bonding role for the lithium-containing phosphate in the positive electrode film layer, and can make the positive electrode plate have a relatively high bonding force and cohesive force, thereby reducing or avoiding the problem of powder shedding of the positive electrode film layer during the die-cutting, winding and hot pressing processes of the positive electrode plate, thereby reducing the self-discharge of the battery and improving the storage performance of the battery.
[0046] It is understood that the weight average molecular weight of the polyacrylate adhesive can be 800,000 Daltons, 850,000 Daltons, 900,000 Daltons, 950,000 Daltons, 1,000,000 Daltons, 1,050,000 Daltons, 1,100,000 Daltons, 1,150,000 Daltons, 1,200,000 Daltons, 1,250,000 Daltons, 1,300,000 Daltons, and any value within the range formed by any two of the above values. The polyacrylate adhesive can be an existing commercially available product. Among them, the weight average molecular weight of 10,000 Daltons = 10 kDa.
[0047] It should be noted that the compaction density reflects the compactness of the battery electrode after being compacted under a certain pressure. The calculation formula for compaction density is: compaction density = surface density / (thickness of the electrode after rolling - thickness of the current collector). Among them, the surface density refers to the weight of the dressing of the positive electrode film layer on the electrode per unit area.
[0048] In some embodiments, the weight average molecular weight of the polyacrylate binder is 1 million Daltons to 1.3 million Daltons. The use of the polyacrylate binder with the weight average molecular weight in the positive electrode film layer is conducive to further improving the bonding force and cohesion of the positive electrode sheet using lithium phosphate as the positive electrode active material, further improving the problem of powder falling of the positive electrode sheet, and further reducing the self-discharge of the battery.
[0049] In some of the embodiments, the polyacrylate binder includes structural units derived from acrylic acid ester monomers, wherein the acrylic acid ester monomers include one or more of methyl methacrylate, butyl acrylate, or isooctyl acrylate.
[0050] In some embodiments, the mass proportion of the structural units derived from acrylate monomers in the polyacrylate adhesive is 60% to 80%. It is understood that the mass proportion of the structural units derived from acrylate monomers in the polyacrylate adhesive can be 60%, 62%, 65%, 68%, 70%, 72%, 75%, 78%, 80%, and any value within the range formed by any two of the above values.
[0051] In some embodiments, the polyacrylate adhesive further includes a structural unit derived from a first monomer, and the first monomer includes one or more of styrene or acrylonitrile. Thus, the structural unit derived from the first monomer is used in the polyacrylate adhesive, styrene contains a benzene ring structure, and acrylonitrile contains a polar nitrile group. After polymerizing them with the acrylic ester monomer, the interaction sites between polymer molecules can be increased, so that the attraction between molecules is enhanced, and the bonding between polymer molecules is tighter, which is conducive to improving the cohesion.
[0052] In some embodiments, the mass proportion of the structural unit derived from the first monomer in the polyacrylate adhesive is 20% to 40%. It is understood that the mass proportion of the structural unit derived from the first monomer in the polyacrylate adhesive may be 20%, 22%, 25%, 28%, 30%, 32%, 35%, 38%, 40%, and any value within the range formed by any two of the above values.
[0053] The polyacrylate binder can be prepared by existing methods or by using existing commercially available products. In some embodiments, the polyacrylate binder can be prepared by the following method: dissolving styrene (St) and methyl methacrylate (MMA) in a solvent, adding an initiator benzoyl peroxide to react and preparing a polymethacrylate binder. The polyacrylate binder does not contain fluorine, which can alleviate the problem of persistent pollution risk and bioaccumulative hazard of batteries.
[0054] In some embodiments, the mass fraction of the polyacrylate binder is 1% to 2% based on the total mass of the positive electrode film layer as 100%. Controlling the mass fraction of the polyacrylate binder in the positive electrode film layer within the above range is beneficial to improving the bonding and cohesive force of the positive electrode sheet while taking into account the energy density of the battery.
[0055] It can be understood that the mass fraction of the polyacrylate binder in the positive electrode film layer can be 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2% and any value within the range formed by any two of the above values.
[0056] In some of the embodiments, the Dv50 particle size of the lithium-containing phosphate is 1.1 μm to 1.8 μm. The use of the lithium-containing phosphate with the above-mentioned Dv50 particle size is conducive to shortening the transmission distance of lithium ions and electrons, and is conducive to the energy output of high-energy-density lithium-ion secondary batteries. The polyacrylate binder of the present application has good adhesion to the lithium-containing phosphate, and the lithium-containing phosphate is combined with the binder to obtain a high-energy-density lithium-ion secondary battery containing lithium phosphate with low self-discharge.
[0057] Among them, Dv50 particle size is also called volume median particle size, which means that in the particle size distribution, 50% of the particles have diameters smaller than this value, and 50% of the particles have diameters larger than this value.
[0058] On the other hand, polyacrylate binders with a weight-average molecular weight of 800,000 Daltons to 1.3 million Daltons easily cause the positive electrode slurry to form gel; at the same time, the positive electrode slurry using lithium phosphate as the positive electrode active material is also prone to gelation itself.
[0059] In this regard, in some embodiments of the present application, the positive electrode film layer also includes a dispersant, and the dispersant includes one or more of a phosphate compound, a styrene-ethylene / butylene-styrene block copolymer, and a hydrogenated nitrile rubber. Using the above-mentioned compounds as dispersants, with the assistance of the above-mentioned dispersants, a polyacrylate binder with a weight average molecular weight of 800,000 Daltons to 1.3 million Daltons is used, which can not only alleviate the problem of gelation of the positive electrode slurry and improve the processing performance of the positive electrode slurry; but also improve the bonding force and cohesion of the positive electrode sheet, alleviate the problem of powder loss of the positive electrode sheet during die cutting, winding and hot pressing, and reduce the self-discharge of the battery.
[0060] Among the above-mentioned dispersants, phosphate compounds are organic compounds containing phosphate functional groups (-OPO(OR)2), where R represents an organic group. Styrene-Ethylene / Butylene-Styrene block copolymer (SEBS) is a linear triblock copolymer with polystyrene as the terminal segment and ethylene-butene copolymer obtained by hydrogenation of polybutadiene as the middle elastic block. Hydrogenated Nitrile Rubbe (HNBR) is a highly saturated special elastomer obtained by hydrogenation of nitrile rubber (NBR).
[0061] In some of the embodiments, the mass fraction of the dispersant is 0.3% to 0.5%, based on the total mass of the positive electrode film layer as 100%. Adding the above-mentioned content of the dispersant to the positive electrode film layer is beneficial to disperse the polyacrylate binder and the lithium-containing phosphate, and effectively improves the gelation phenomenon of the positive electrode slurry. It can be understood that the mass fraction of the dispersant in the positive electrode film layer can be 0.3%, 0.32%, 0.35%, 0.38%, 0.4%, 0.42%, 0.45%, 0.48%, 0.5% and any value within the range formed by any two of the above values.
[0062] In some of the embodiments, the positive electrode plate also includes a positive electrode current collector and a primer layer, the primer layer is arranged between the positive electrode current collector and the positive electrode film layer, the primer layer includes a conductive agent and a polar group grafted modified polymer binder, the polar group grafted modified polymer binder includes a polar group, and the polar group includes a carboxyl group and / or an ester group.
[0063] By setting a primer between the positive electrode current collector and the positive electrode film layer, a polar group grafted modified polymer binder is used in the primer; the polar group grafted modified polymer binder has good adhesion not only to the positive electrode current collector, but also to the positive electrode film layer, which is conducive to further improving the adhesion of the positive electrode plate and further improving the problem of plate powder falling. It can be understood that the polar group grafted modified polymer binder can use an existing commercially available binder. The positive electrode current collector can be an aluminum foil current collector.
[0064] In some of the embodiments, the polar group grafted modified polymer binder includes a structural unit derived from a second monomer and a structural unit derived from a third monomer; the second monomer and the third monomer are of different monomer types; the second monomer includes one or more of styrene or acrylonitrile; the third monomer includes one or more of ethylene, propylene, butadiene, isoprene or acrylonitrile.
[0065] In some embodiments, the polar group grafted modified polymer binder includes one or more of polar group grafted modified styrene-ethylene / butylene-styrene block copolymer, polar group grafted modified hydrogenated styrene-butadiene rubber, polar group grafted modified styrene-isoprene-styrene block copolymer or polar group grafted modified styrene-ethylene-propylene-styrene type block copolymer. The use of the above polymer binder in the primer layer is conducive to the good adhesion between the primer layer and the positive electrode film layer, and at the same time, the positive electrode plate has a certain pressure-sensitive property, which helps to maintain good contact between the electrode materials, improve the charge transfer efficiency, and enable the plate to better adapt to the pressure changes inside the battery.
[0066] Among the above-mentioned polymer binders, Styrene-Ethylene / Butylene-Styrene block copolymer (SEBS) is a linear triblock copolymer with polystyrene as the terminal segment and ethylene-butene copolymer obtained by hydrogenating polybutadiene as the middle elastic block; Hydrogenated Styrene Butadiene Rubber (HSBR) is a thermoplastic elastomer prepared by modifying styrene butadiene rubber using hydrogenation technology; Styrene-Isoprene-Styrene block copolymer (SIS) is an important thermoplastic elastomer material; Styrene-Ethylene / Propylene-Styrene Block Copolymer (SEPS) is a product obtained by selective hydrogenation of styrene-isoprene polymer.
[0067] In some of the embodiments, the polar group grafted modified polymer binder includes a structural unit derived from a fourth monomer containing a polar group, and the fourth monomer includes one or more of acrylic acid, methyl methacrylate, butyl acrylate, isooctyl acrylate, or maleic anhydride. That is, the polar group grafted modified polymer binder can be a binder formed by grafting and modifying a polymer with one or more raw materials of acrylic acid, methyl methacrylate, butyl acrylate, isooctyl acrylate, or maleic anhydride. Polar groups such as carboxyl groups and ester groups are introduced into the polymer through the above compounds, thereby improving the bonding force between the polymer binder and the positive electrode current collector.
[0068] In some embodiments, the mass fraction of the polar group grafted modified polymer binder is 50% to 70% based on the total mass of the primer layer as 100%. Controlling the content of the polar group grafted modified polymer binder in the primer layer within the above range is more conducive to having good adhesion between the primer layer and the positive electrode current collector and the positive electrode film layer, so that the positive electrode sheet as a whole has good adhesion.
[0069] It can be understood that the mass fraction of the polar group grafted modified polymer binder can be 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, 60%, 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, 69%, 70% and any value within the range formed by any two of the above values.
[0070] In some embodiments, the thickness of the primer layer is 1 μm to 2 μm. It is understood that the thickness of the primer layer can be 1 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm, 1.6 μm, 1.7 μm, 1.8 μm, 1.9 μm, 2 μm, and any value within the range formed by any two of the above values.
[0071] In some embodiments, the mass fraction of the lithium-containing phosphate is 90% to 99% based on the total mass of the positive electrode film layer being 100%. The lithium-containing phosphate in the positive electrode film layer may be one or more of lithium iron phosphate, lithium manganese phosphate or lithium manganese iron phosphate.
[0072] In one embodiment of the present application, a positive electrode plate is provided, the positive electrode plate includes a positive electrode film layer, the positive electrode film layer includes a lithium-containing phosphate and a polyacrylate binder, and the weight average molecular weight of the polyacrylate binder is 800,000 Daltons to 1.3 million Daltons. The above-mentioned positive electrode plate is not prone to powder shedding, which can reduce battery self-discharge.
[0073] In one embodiment of the present application, a positive electrode slurry is provided, the positive electrode slurry includes a lithium-containing phosphate, a polyacrylate binder and an organic solvent, the weight average molecular weight of the polyacrylate binder is 800,000 Daltons to 1.3 million Daltons. The positive electrode sheet prepared by using the positive electrode slurry is not prone to powder shedding, which can reduce battery self-discharge.
[0074] In some embodiments, the organic solvent includes one or more of N-methylpyrrolidone (NMP), dimethyl sulfoxide (DMSO), N,N-dimethylformamide (DMF) or triethyl phosphate (TEP). The use of the above organic solvents is more conducive to improving the dispersion uniformity and coating uniformity of the positive electrode slurry.
[0075] In some embodiments, the positive electrode slurry further includes a dispersant, and the dispersant includes one or more of a phosphate compound, a styrene-ethylene / butylene-styrene block copolymer, or a hydrogenated nitrile rubber. In this way, the positive electrode slurry is not easy to gel, and the dispersion uniformity and coating uniformity of the positive electrode slurry are improved.
[0076] In one embodiment of the present application, an electric device is provided, and the electric device includes the lithium-ion secondary battery described above in the present application.
[0077] The lithium ion secondary battery and the electric device of the present application will be described below with reference to the drawings as appropriate.
[0078] In one embodiment of the present application, a lithium ion secondary battery is provided.
[0079] Generally, lithium-ion secondary batteries include a positive electrode sheet, a negative electrode sheet, an electrolyte, and a separator. During the battery charging and discharging process, active ions are embedded and extracted back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is set between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.
[0080] The positive electrode plate includes a positive electrode current collector and a positive electrode film layer arranged on at least one surface of the positive electrode current collector.
[0081] As a non-limiting example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.
[0082] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material base layer. The composite current collector may be obtained by forming a metal material on a polymer material substrate. In the positive electrode current collector, non-limiting examples of the metal material may include one or more of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. In the positive electrode current collector, non-limiting examples of the polymer material substrate may include one or more of substrates such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.
[0083] In some embodiments, the positive electrode active material mainly includes lithium-containing phosphates, and may also include other positive electrode active materials for lithium-ion secondary batteries known in the art. Among them, non-limiting examples of lithium-containing phosphates may include, but are not limited to, one or more of lithium iron phosphate, a composite material of lithium iron phosphate and carbon, lithium manganese phosphate, a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.
[0084] As a non-limiting example, other positive electrode active materials for lithium-ion secondary batteries may include lithium transition metal oxides and modified compounds thereof. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Among them, examples of lithium transition metal oxides may include, but are not limited to, one or more of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide and modified compounds thereof. Non-limiting examples of lithium cobalt oxides may include LiCoO2; non-limiting examples of lithium nickel oxides may include LiNiO2; non-limiting examples of lithium manganese oxides may include LiMnO2, LiMn2O4, etc.; non-limiting examples of lithium nickel cobalt manganese oxides may include LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also referred to as NCM 333 )、LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM 523 )、LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM 211 )、LiNi 0.6 Co 0.2 Mn0.2 O2 (also referred to as NCM 622 )、LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM 811 ) etc.; Non-limiting examples of lithium nickel cobalt aluminum oxide may include LiNi 0.85 Co 0.1 Al 0.05 O2.
[0085] It is understandable that the battery will be accompanied by lithium (Li) deintercalation and consumption during the charging and discharging process, and the content of Li in the positive electrode plate is different when the battery is discharged to different states. In the list of positive electrode materials in this application, unless otherwise specified, the content of Li is the initial state of the material. The positive electrode material is applied to the positive electrode plate in the battery system, and after the charge and discharge cycle, the content of Li in the positive electrode material contained in the plate usually changes. Among them, the content of Li can be measured by molar content, but is not limited to this. Regarding "the content of Li is the initial state of the material", the initial state of the material refers to the state before the material is added to the positive electrode slurry. It is understandable that the new material obtained by appropriate modification on the basis of the listed positive electrode materials is also within the scope of the positive electrode material. The aforementioned appropriate modification refers to the acceptable modification method for the positive electrode material, and non-limiting examples include coating modification.
[0086] In the list of positive electrode materials in this application, the content of oxygen (O) is only a theoretical state value. The release of oxygen from the lattice will cause the molar content of oxygen to change, and the actual content of O will fluctuate. Among them, the content of O can be measured by molar content, but is not limited to this.
[0087] The weight ratio of the positive electrode active material in the positive electrode film layer is 80 wt % or more, based on the total weight of the positive electrode film layer.
[0088] In some embodiments, the positive electrode film layer further includes a polyacrylate binder and a dispersant.
[0089] In some embodiments, the positive electrode film layer may further include a conductive agent. As a non-limiting example, the conductive agent may include one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers. The weight ratio of the conductive agent in the positive electrode film layer is 0 wt % to 20 wt %, based on the total weight of the positive electrode film layer.
[0090] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder, the dispersant and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry, the positive electrode slurry is coated on both sides of the positive electrode collector, and the positive electrode sheet is formed after drying and cold pressing by a cold rolling mill.
[0091] In some embodiments, a primer layer is further disposed between the positive electrode current collector and the positive electrode film layer.
[0092] The negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode active material layer includes a negative electrode active material.
[0093] As a non-limiting example, the negative electrode current collector has two surfaces opposite to each other in its own thickness direction, and the negative electrode active material layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.
[0094] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be obtained by forming a metal material on a polymer material substrate. Among them, in the negative electrode current collector, non-limiting examples of the metal material may include one or more of copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. In the negative electrode current collector, non-limiting examples of the polymer material substrate may include one or more of substrates such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.
[0095] In some embodiments, the negative electrode active material may be a negative electrode active material for a battery known in the art.
[0096] As a non-limiting example, the negative electrode active material of the lithium ion secondary battery may include one or more of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. Silicon-based materials may include one or more of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. Tin-based materials may include one or more of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.
[0097] In some embodiments, the negative electrode active material layer may further include a binder. The binder may include one or more of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).
[0098] In some embodiments, the negative electrode active material layer may further include a conductive agent, which may include one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0099] In some embodiments, the negative electrode active material layer may further optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).
[0100] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (a non-limiting example of the solvent is deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on at least one side of the surface of the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained. The surface of the negative electrode collector coated with the negative electrode slurry can be on a single surface of the negative electrode collector or on both surfaces of the negative electrode collector. The solid content of the negative electrode slurry can be 40wt%~60wt%. The viscosity of the negative electrode slurry at room temperature can be adjusted to 2000mPa·s~10000mPa·s. When coating the negative electrode slurry, the coating unit surface density on a dry weight basis (excluding the solvent) can be 75g / m 2 ~220g / m 2 The compaction density of the negative electrode sheet can be 1.0g / cm 3 ~1.8g / cm 3 .
[0101] The electrolyte has the function of conducting ions between the positive electrode and the negative electrode. The present application has no particular restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.
[0102] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.
[0103] In some embodiments, the electrolyte salt of the lithium ion secondary battery may include one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bisfluorosulfonyl imide (LiFSI), lithium bistrifluoromethanesulfonyl imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorobisoxalatophosphate (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP).
[0104] In some embodiments, the solvent may include one or more of fluoroethylene carbonate (FEC), ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS), and diethyl sulfone (ESE).
[0105] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.
[0106] In some embodiments, the additive in the electrolyte may include, but is not limited to, one or more of fluoroethylene carbonate (FEC), difluoroethylene carbonate (DFEC), trifluoromethylethylene carbonate (TFPC), and the like.
[0107] In some embodiments, the lithium-ion secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.
[0108] In some embodiments, the material of the isolation membrane may include one or more of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane may be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer may be the same or different, without particular limitation.
[0109] In some embodiments, the thickness of the isolation film is 6 μm to 40 μm, and may be 12 μm to 20 μm.
[0110] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.
[0111] In some embodiments, the lithium-ion secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.
[0112] In some embodiments, the outer packaging of the lithium ion secondary battery can be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the lithium ion secondary battery can also be a soft package, such as a bag-type soft package. The material of the soft package can be plastic, and further, non-limiting examples of plastic can include one or more of polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0113] A lithium-ion secondary battery includes at least one battery cell. A lithium-ion secondary battery may include one or more battery cells.
[0114] In this application, unless otherwise specified, "battery cell" refers to a basic unit that can realize the mutual conversion of chemical energy and electrical energy, and further, generally speaking, at least includes a positive electrode sheet, a negative electrode sheet and an electrolyte. During the battery charging and discharging process, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting active ions between the positive electrode sheet and the negative electrode sheet.
[0115] The present application has no particular limitation on the shape of the battery cell, which may be cylindrical, square or any other shape. Figure 1 The battery cell 5 is a square structure as an example.
[0116] In some embodiments, reference Figure 2 , the outer packaging may include a shell 51 and a cover plate 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. The number of electrode assemblies 52 contained in the battery cell 5 can be one or more, and those skilled in the art can select according to specific actual needs.
[0117] In some embodiments, the battery cells 5 can be assembled into a battery module. The number of battery cells 5 contained in the battery module can be one or more, and the specific number can be selected by those skilled in the art according to the application and capacity of the battery module.
[0118] In the battery module, the plurality of battery cells 5 may be arranged in sequence along the length direction of the battery module. Of course, they may also be arranged in any other manner. Further, the plurality of battery cells 5 may be fixed by fasteners.
[0119] Optionally, the battery module may further include a housing having a receiving space, and the plurality of battery cells 5 are received in the receiving space.
[0120] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery pack.
[0121] The battery pack may include a battery box and a plurality of battery modules disposed in the battery box. The battery box includes an upper box body and a lower box body, and the upper box body can be covered on the lower box body to form a closed space for accommodating the battery modules. The plurality of battery modules can be arranged in the battery box in any manner.
[0122] In addition, the present application also provides an electrical device, which includes at least one of the lithium-ion secondary battery, battery module, or battery pack provided in the present application. The lithium-ion secondary battery, battery module, or battery pack can be used as a power source for the electrical device, and can also be used as an energy storage unit for the electrical device. The electrical device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited to these.
[0123] As an electrical device, a lithium-ion secondary battery, a battery module or a battery pack can be selected according to its usage requirements.
[0124] Figure 3 The power consumption device 6 is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. In order to meet the power consumption device's requirements for high power and high energy density of lithium-ion secondary batteries, a battery pack or a battery module can be used.
[0125] Another example of a device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be thin and light, and a lithium-ion secondary battery may be used as a power source.
[0126] The following are some examples.
[0127] In order to make the technical problems, technical solutions and beneficial effects solved by the present application clearer, the present application will be further described in detail below in conjunction with the embodiments and drawings. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present application and its applications. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.
[0128] If no specific techniques or conditions are specified in the examples, the techniques or conditions described in the literature in the field or the product instructions are used. If no manufacturer is specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0129] Embodiment 1:
[0130] (1) Preparation of positive electrode
[0131] The positive electrode active material LiFePO4 (LFP), polymethyl methacrylate binder, dispersant SEBS model 1701 produced by Kraton Corporation of the United States, and conductive agent carbon black (Super P) are mixed in a mass ratio of 97:1:0.5:1.5, and the solvent N-methylpyrrolidone is added and mixed evenly to obtain a positive electrode slurry with a solid content of 65%; the above-mentioned positive electrode slurry is coated on the double-sided surface of the aluminum foil current collector with the same coating thickness on both sides, and the positive electrode sheet is obtained through drying, cold pressing, striping, cutting and other processes. The single-sided coating surface density of the positive electrode film layer in the positive electrode sheet is 25mg / cm 2 The compaction density of the positive electrode is 2.5g / cm 3 The Dv50 particle size of the positive electrode active material LiFePO4 is 1.5μm.
[0132] The preparation method of polymethyl methacrylate binder is as follows: add 108mL distilled water, 0.005g polyvinyl alcohol, 0.009g sodium dodecylbenzene sulfonate into a 500mL flask, keep the water bath at 81°C, and stir for 0.5h; then add 0.66g benzoyl peroxide, 14.14g methyl methacrylate, 3.608g acrylonitrile, keep the temperature at 81°C, react for 1.5h, wash the polymer product with cold water, and filter it. The product polymethyl methacrylate binder is obtained. The weight average molecular weight of the polymethyl methacrylate binder is 1 million Daltons.
[0133] (2) Preparation of negative electrode
[0134] The negative electrode active material artificial graphite, the thickener sodium carboxymethyl cellulose, the binder styrene-butadiene rubber, and the conductive agent carbon black (Super P) are mixed in a mass ratio of 97:1:1:1, and deionized water is added. The negative electrode slurry is obtained under the action of a vacuum mixer, and the solid content of the negative electrode slurry is 50%; the negative electrode slurry is evenly coated on the double-side surface of the copper foil current collector; the copper foil is dried at room temperature and then transferred to a 120°C oven for drying for 1 hour, and then cold pressed and cut to obtain the negative electrode sheet.
[0135] (3) Isolation film
[0136] A polypropylene film with a thickness of 12 μm was selected as the isolation film.
[0137] (4) Electrolyte
[0138] Ethylene carbonate (EC) and ethyl methyl carbonate (EMC) are mixed at a mass ratio of 30:70 to obtain an organic solvent, and fully dried LiPF6 is dissolved in the organic solvent to prepare an electrolyte with a LiPF6 concentration of 1 mol / L.
[0139] (5) Battery assembly
[0140] The positive electrode sheet, separator and negative electrode sheet are wound into an electrode assembly, and the separator is located between the positive electrode sheet and the negative electrode sheet to play an isolating role. The electrode assembly is placed in an outer package, injected with the above electrolyte and packaged, and then the battery is formed after standing, hot and cold pressing, forming, clamping, and capacity separation.
[0141] Embodiment 2:
[0142] This embodiment is basically the same as embodiment 1, except that: in step (1), the preparation method of polymethyl methacrylate binder is as follows: add 108 mL of distilled water and 0.005 g of polyvinyl alcohol and 0.009 g of sodium dodecylbenzene sulfonate to a 500 mL flask, keep the water bath at 81°C, and stir for 0.5 h; then add 0.99 g of benzoyl peroxide, 14.14 g of methyl methacrylate, and 3.608 g of acrylonitrile, keep the temperature at 81°C, react for 1.5 h, wash the polymer product with cold water, and filter. The product polymethyl methacrylate binder is obtained. The weight average molecular weight of the polymethyl methacrylate binder is 800,000 Daltons.
[0143] Embodiment 3:
[0144] This embodiment is basically the same as embodiment 1, except that: in step (1), the preparation method of polymethyl methacrylate binder is as follows: add 108 mL of distilled water and 0.005 g of polyvinyl alcohol and 0.009 g of sodium dodecylbenzene sulfonate to a 500 mL flask, keep the water bath at 81°C, and stir for 0.5 h; then add 0.462 g of benzoyl peroxide, 14.14 g of methyl methacrylate, and 3.608 g of acrylonitrile, keep the temperature at 81°C, react for 1.5 h, wash the polymer product with cold water, and filter. The product polymethyl methacrylate binder is obtained. The weight average molecular weight of the polymethyl methacrylate binder is 1.3 million Daltons.
[0145] Embodiment 4:
[0146] This embodiment is basically the same as the embodiment 1, except that in step (1), the mass ratio of the positive electrode active material LFP, the polymethyl methacrylate binder, the dispersant SEBS and the conductive agent carbon black (Super P) is 97:1.8:0.5:0.7; wherein the amount of the polymethyl methacrylate binder is 1.8%.
[0147] Embodiment 5:
[0148] This embodiment is basically the same as the embodiment 1, except that: in step (1), the mass ratio of the positive electrode active material LFP, the polymethyl methacrylate binder, the dispersant SEBS and the conductive agent carbon black (Super P) is 97:2:0.5:0.5; wherein the amount of the polymethyl methacrylate binder is 2%.
[0149] Embodiment 6:
[0150] This embodiment is basically the same as the embodiment 1, except that: in step (1), a phosphate dispersant of model BYK-110 produced by BYKChemie of Germany is used instead of the dispersant SEBS; the single-side coating surface density of the positive electrode film layer in the positive electrode sheet is 30 mg / cm 2 The compaction density of the positive electrode is 2.45g / cm 3 The Dv50 particle size of the positive electrode active material LiFePO4 is 1.8μm.
[0151] Embodiment 7:
[0152] This embodiment is basically the same as the embodiment 1, except that: in step (1), the mass ratio of the positive electrode active material LFP, the polymethyl methacrylate binder, the dispersant SEBS and the conductive agent carbon black (Super P) is 97:1:0.3:1.7; the amount of the dispersant SEBS is 0.3%; the single-side coating surface density of the positive electrode film layer in the positive electrode sheet is 20 mg / cm 2 The compaction density of the positive electrode is 2.55g / cm3 The Dv50 particle size of the positive electrode active material LiFePO4 is 1.1 μm.
[0153] Embodiment 8:
[0154] This embodiment is basically the same as embodiment 1, except that: the method for preparing the positive electrode sheet in step (1) is as follows:
[0155] (1.1) Preparation of base coating
[0156] The acrylic acid graft modified SEBS binder and the conductive agent carbon black (Super P) were mixed in a mass ratio of 70:30, N-methylpyrrolidone (NMP) was added and stirred in a double planetary stirrer for 3 hours to prepare a primer slurry with a solid content of 20%, and then the primer slurry was scraped on the double-side surface of a 13-micron thick aluminum foil current collector, dried, and formed a primer on the current collector. The thickness of the single-side primer is 2μm. Among them, the acrylic acid graft modified SEBS binder uses a product model 1924 produced by Kraton Corporation of the United States.
[0157] (1.2) Preparation of positive electrode film
[0158] The positive electrode active material LFP, polymethyl methacrylate binder, dispersant SEBS and conductive agent carbon black (SuperP) were mixed in a mass ratio of 97:1:0.5:1.5, and the solvent N-methylpyrrolidone was added and mixed evenly to obtain a positive electrode slurry; the above-mentioned positive electrode slurry was coated on the primer layer of the aluminum foil current collector with primer layer prepared above to prepare a positive electrode film layer, and the coating thickness on both sides was the same, wherein the primer layer was arranged between the current collector and the positive electrode film layer, and the positive electrode plate was obtained through drying, cold pressing, striping, cutting and other processes. The single-sided coating surface density of the positive electrode film layer in the positive electrode plate is 25mg / cm 2 The weight average molecular weight of the polymethyl methacrylate binder is 1 million Daltons, and the preparation method is the same as that of Example 1.
[0159] Embodiment 9:
[0160] This embodiment is basically the same as Embodiment 8, except that in step (1.1), the mass ratio of acrylic acid grafted modified SEBS binder to conductive agent carbon black (Super P) is 50:50.
[0161] Embodiment 10:
[0162] This embodiment is basically the same as Embodiment 8, except that the thickness of the primer layer in step (1.1) is 1 μm.
[0163] Embodiment 11:
[0164] This embodiment is basically the same as embodiment 8, except that: lithium iron manganese phosphate LiMn is used in step (1.2) 0.6 Fe 0.4 O4 replaces LFP as the positive electrode active material.
[0165] Embodiment 12:
[0166] This embodiment is basically the same as Embodiment 3, except that in step (1), poly(2-ethylhexyl acrylate) with the same weight average molecular weight is used instead of poly(methyl methacrylate) as the binder.
[0167] The preparation method of polyisooctyl acrylate binder is as follows: add 108 mL of distilled water, 0.005 g of polyvinyl alcohol, and 0.009 g of sodium dodecylbenzene sulfonate into a 500 mL flask, keep the water bath at 81° C., and stir for 0.5 h; then add 0.66 g of benzoyl peroxide, 13.2 g of isooctyl acrylate, and 3.608 g of acrylonitrile, keep the temperature at 81° C., react for 1.5 h, wash the polymer product with cold water, and filter it by suction to obtain the product polyisooctyl acrylate binder.
[0168] Comparative Example 1:
[0169] This comparative example is basically the same as Example 2, except that: the preparation method of the polymethyl methacrylate binder in step (1) is as follows: 108 mL of distilled water, 0.005 g of polyvinyl alcohol, and 0.009 g of sodium dodecylbenzene sulfonate are added to a 500 mL flask, the water bath is kept at 81°C, and stirred for 0.5 h; then 1.05 g of benzoyl peroxide, 14.14 g of methyl methacrylate, and 3.608 g of acrylonitrile are added, the temperature is kept at 81°C, the reaction is carried out for 1.5 h, the polymerization product is washed with cold water, and suction filtered. The product polymethyl methacrylate binder is obtained. The weight average molecular weight of the polymethyl methacrylate binder is 600,000 Daltons.
[0170] Comparative Example 2:
[0171] This comparative example is basically the same as Example 1, except that: the preparation method of the polymethyl methacrylate binder in step (1) is as follows: 108 mL of distilled water, 0.005 g of polyvinyl alcohol, and 0.009 g of sodium dodecylbenzene sulfonate are added to a 500 mL flask, the water bath is kept at 81°C, and stirred for 0.5 h; then 0.38 g of benzoyl peroxide, 14.14 g of methyl methacrylate, and 3.608 g of acrylonitrile are added, the temperature is kept at 81°C, the reaction is performed for 1.5 h, the polymerization product is washed with cold water, and filtered. The product polymethyl methacrylate binder is obtained. The weight average molecular weight of the polymethyl methacrylate binder is 1.5 million Daltons. Due to the gelation phenomenon of the positive electrode slurry, it is impossible to make a uniform slurry, and the positive electrode sheet and battery are not prepared.
[0172] Test method:
[0173] (1) Pole brittleness test
[0174] Take a 20mm×100mm (longitudinal) sample of the prepared positive electrode sheet and sample along the rolling direction of the electrode sheet; place the pre-folded experimental electrode sheet on the flat surface of the experimental table and roll it with a 2kg cylindrical roller. After each rolling, observe whether the electrode sheet is light-transmitting. When the electrode sheet is light-transmitting, record the corresponding number of rolling times. The number of rolling times indicates the brittleness of the electrode sheet.
[0175] (2) Electrode mechanical properties test
[0176] (2.1) Adhesion
[0177] The prepared positive electrode sheet is cut into test specimens of 20mm×100mm size for later use; one side of the double-sided tape is pasted to the surface of the steel plate, and the other side is adhered to the electrode to be tested, and compacted with a roller to make it completely fit with the electrode; one end of the current collector is reversely bent with a bending angle of 180°; a high-speed rail tensile testing machine is used for testing, one end of the steel plate is fixed to the lower fixture of the tensile testing machine, and the bent end of the current collector is fixed to the upper fixture, the angle of the current collector is adjusted to ensure that the upper and lower ends are in a vertical position, and then the sample is stretched at a speed of 50mm / min until the current collector is completely peeled off from the surface of the electrode, the displacement and force in the process are recorded, and the force when the force is balanced is taken as the bonding force of the electrode.
[0178] (2.2) Cohesion
[0179] The prepared positive electrode sheet is cut into test specimens of 20mm×100mm size for later use; one side of the double-sided tape is pasted to the surface of the steel plate, and the other side is pasted to the electrode to be tested, and compacted with a roller to make it completely fit with the electrode; affix a special tape for cohesion test on the other side of the electrode and compact it with a roller; bend one end of the special tape for cohesion in the opposite direction with a bending angle of 180°; use a high-speed rail tensile testing machine for testing, fix one end of the steel plate to the clamp below the tensile testing machine, fix the bent end of the current collector to the clamp above, adjust the angle of the current collector to ensure that the upper and lower ends are in a vertical position, and then stretch the sample at a speed of 50mm / min until the current collector is completely peeled off from the surface of the electrode, record the displacement and force in the process, and take the force when the force is balanced as the cohesion of the electrode.
[0180] (3) Weight average molecular weight test
[0181] The binder was dissolved in NMP solvent, and the weight average molecular weight of the polymer was measured using gel permeation chromatography.
[0182] (4) Battery self-discharge performance test
[0183] The battery cell was left at room temperature for 1 hour, and the initial open circuit voltage (OCV) value of the battery cell was tested with a 6.5-digit digital multimeter, recorded as OCV1; after the test, the battery cell was left at 45°C for 48 hours, and then left at room temperature for 1 hour, and the open circuit voltage value was tested again, recorded as OCV2, and the self-discharge rate was calculated. The calculation formula for the self-discharge rate is: (OCV2-OCV1) / 48. Measure 10 battery cells and take the average value.
[0184] (5) Cathode film coating surface density test
[0185] The coating surface density is tested using the following method: punch out 15 positive electrode sheets and current collectors (the same production batch number as the current collector used for the positive electrode sheets) of a certain area S (in cm2), weigh the mass, and calculate the average value. The average mass of the positive electrode sheet is M1 (in mg), and the average mass of the current collector is M2 (in mg); when the positive electrode film layer is set on both sides of the current collector, the coating surface density is: (M1-M2) / 2S.
[0186] (6) Volume average particle size Dv50 test
[0187] Take a clean beaker, add an appropriate amount of the particle sample to be tested, and use 120W ultrasound for 5 minutes to ensure that the sample is completely dispersed. The test instrument is Malvern 2000 from the United States. After the sample is poured into the injection tower, it circulates with the solution to the test optical path system. When the particles are irradiated by the laser beam, the particle size distribution characteristics of the particles can be obtained by receiving and measuring the energy distribution of the scattered light (shading degree: 8%~12%). Draw a particle size volume distribution diagram based on the test data, and it can be obtained from the distribution diagram that: the diameter of particles accounting for 50% of the total volume is greater than a certain Dv50 value, and the diameter of particles accounting for 50% of the total volume is less than this Dv50 value, then this Dv50 value is the volume average particle size of the particles.
[0188] (7) Pole compaction density test
[0189] Disassemble the battery cell to take out the positive electrode sheet, and punch it into 1540.25mm 2 Take another layer of electrode, wipe off the surface membrane layer and the remaining empty current collector foil, and also punch it into 1540.25mm 2 Take a small disc and weigh the mass M0 of the empty current collector foil. Then the compaction density PD = (M-M0) / 1.54025 / n / (L-L0), where n is the number of film layers coated on the current collector, which is 1 or 2, 1 for single-sided coating and 2 for double-sided coating. L0 is the thickness of the current collector foil.
[0190] The parameters and performance data of the lithium-ion secondary batteries of the above embodiments and comparative examples are shown in Table 1, Table 2 and Table 3. " / " in the table means that it does not exist or is not tested. Among them, the molecular weight of the polyacrylate binder and the molecular weight of the modified polymer binder are all rounded values.
[0191] Table 1
[0192]
[0193] Table 2
[0194]
[0195] Table 3
[0196]
[0197] It can be seen from the data in the table that the self-discharge of the lithium-ion secondary battery of the present application is small. Compared with Examples 1 to 12, the molecular weight of the polyacrylate binder in Comparative Example 1 is too small, the bonding force is poor, and the battery self-discharge is large. In Comparative Example 2, the molecular weight of the polyacrylate binder is too large, the positive electrode slurry has a gel phenomenon, and it cannot be made into a uniform slurry, and the processing performance is poor.
[0198] The above description of various embodiments tends to emphasize the differences between the various embodiments. The same or similar aspects can be referenced to each other, and for the sake of brevity, they will not be repeated herein.
[0199] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A lithium ion secondary battery, characterized in that: The positive electrode sheet comprises a positive electrode current collector and a positive electrode film layer provided on at least one side of the positive electrode current collector, and the coating surface density of the positive electrode film layer on one side is 20 mg / cm 2 ~30mg / cm 2 The positive electrode film layer includes lithium phosphate and polyacrylate binder, the weight average molecular weight of the polyacrylate binder is 800,000 Daltons to 1.3 million Daltons; the compaction density of the positive electrode sheet is 2.45 g / cm 3 ~2.55g / cm 3 .
2. The lithium ion secondary battery according to claim 1, characterized in that: The weight average molecular weight of the polyacrylate binder is 1 million Daltons to 1.3 million Daltons.
3. The lithium ion secondary battery according to claim 1, characterized in that: The polyacrylate adhesive includes a structural unit derived from an acrylic acid ester monomer, and the acrylic acid ester monomer includes one or more of methyl methacrylate, butyl acrylate or isooctyl acrylate.
4. The lithium ion secondary battery according to claim 3, characterized in that: The mass proportion of the structural unit derived from the acrylic ester monomer in the polyacrylate adhesive is 60% to 80%. 5 . The lithium-ion secondary battery according to claim 1 , wherein the polyacrylate binder further comprises a structural unit derived from a first monomer, wherein the first monomer comprises one or more of styrene or acrylonitrile.
6. The lithium ion secondary battery according to claim 5, characterized in that: The mass proportion of the structural unit derived from the first monomer in the polyacrylate adhesive is 20% to 40%.
7. The lithium ion secondary battery according to any one of claims 1 to 6, characterized in that Taking the total mass of the positive electrode film layer as 100%, the mass fraction of the polyacrylate binder is 1% to 2%.
8. The lithium ion secondary battery according to any one of claims 1 to 6, characterized in that The Dv50 particle size of the lithium-containing phosphate is 1.1 μm to 1.8 μm.
9. The lithium ion secondary battery according to any one of claims 1 to 6, characterized in that The positive electrode film layer further includes a dispersant, and the dispersant includes one or more of a phosphate compound, a styrene-ethylene / butylene-styrene block copolymer or a hydrogenated nitrile rubber.
10. The lithium ion secondary battery according to claim 9, characterized in that: Taking the total mass of the positive electrode film layer as 100%, the mass fraction of the dispersant is 0.3% to 0.5%.
11. The lithium ion secondary battery according to any one of claims 1 to 6 and 10, characterized in that: The positive electrode plate also includes a positive electrode current collector and a primer layer, wherein the primer layer is arranged between the positive electrode current collector and the positive electrode film layer, and the primer layer includes a conductive agent and a polar group grafted modified polymer binder, wherein the polar group grafted modified polymer binder includes a polar group, and the polar group includes a carboxyl group and / or an ester group.
12. The lithium ion secondary battery according to claim 11, characterized in that: The polar group graft-modified polymer binder includes a structural unit derived from a second monomer and a structural unit derived from a third monomer; the second monomer and the third monomer are of different monomer types; The second monomer includes one or more of styrene or acrylonitrile; The third monomer includes one or more of ethylene, propylene, butadiene, isoprene or acrylonitrile.
13. The lithium ion secondary battery according to claim 11, characterized in that: The polar group grafted modified polymer binder includes one or more of polar group grafted modified styrene-ethylene / butylene-styrene block copolymer, polar group grafted modified hydrogenated styrene-butadiene rubber, polar group grafted modified styrene-isoprene-styrene block copolymer or polar group grafted modified styrene-ethylene-propylene-styrene type block copolymer.
14. The lithium ion secondary battery according to claim 11, characterized in that: The polar group graft-modified polymer binder includes a structural unit derived from a fourth monomer containing a polar group, and the fourth monomer includes one or more of acrylic acid, methyl methacrylate, butyl acrylate, isooctyl acrylate or maleic anhydride.
15. The lithium ion secondary battery according to claim 11, characterized in that: Based on the total mass of the primer layer being 100%, the mass fraction of the polar group graft-modified polymer binder is 50% to 70%.
16. The lithium ion secondary battery according to claim 11, characterized in that: The thickness of the primer layer is 1 μm to 2 μm.
17. The lithium ion secondary battery according to any one of claims 1 to 6, 10, and 12 to 16, characterized in that: Taking the total mass of the positive electrode film layer as 100%, the mass fraction of the lithium-containing phosphate is 90% to 99%.
18. The lithium ion secondary battery according to any one of claims 1 to 6, 10, and 12 to 16, characterized in that: The lithium-containing phosphate includes one or more of lithium iron phosphate, lithium manganese phosphate or lithium manganese iron phosphate.
19. An electrical device, characterized in that: A lithium ion secondary battery comprising the lithium ion secondary battery according to any one of claims 1 to 18.
Citation Information
Patent Citations
Binder composition for positive electrodes of lithium ion secondary batteries, slurry composition for positive electrodes of lithium ion secondary batteries and production method therefor, production method for positive electrodes of lithium ion secondary batteries, and lithium ion secondary battery
CN105247716A
Binder for all-solid lithium ion secondary battery, electrolyte membrane, electrode membrane, battery, and preparation method
CN109599561A
Positive electrode slurry, positive electrode plate and secondary battery comprising positive electrode plate
CN116745937A
Positive electrode binder and application thereof in lithium battery positive electrode
CN118894967A
Positive electrode for secondary battery and secondary battery comprisign the same
KR1020150037308A
Cited By
Lithium-ion secondary battery and electric apparatus
WO2026103089A1
Solid-state battery and preparation method therefor, positive electrode slurry, positive electrode sheet, and electric device
WO2026144556A1
